Analisis Pengembangan Bisnis menggunakan Business Model Canvas melalui Pendekatan SWOT pada UMKM Kerupuk Gendar Benang Raja Kabupaten Bogor - Kelsha Berliana Rifty; Danang Kusnanto; Rabhi Fathan Muhammad (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
is study aims to analyze the business development of the Gendar Benang Raja Crackers MSME in Bogor Regency using the Business Model Canvas (BMC) approach and SWOT analysis to formulate a sustainable business development strategy. The research method used is a qualitative descriptive method with data collection techniques through direct observation and in-depth interviews with business owners. Data analysis was carried out by mapping the nine elements of the Business Model Canvas, identifying internal and external factors through SWOT analysis, and compiling the IFAS, EFAS, SWOT, and Internal-External (IE) Matrix. The results of the study indicate that the Gendar Benang Raja Crackers MSME has the main strengths of a distinctive traditional taste, affordable prices, the use of raw materials without harmful preservatives, and good relationships with customers. On the other hand, weaknesses found include limited product innovation, unattractive packaging, low digital marketing, limited production capacity, and unstructured business management. Business development opportunities are supported by increasing public interest in traditional products, the development of digital technology, partnership opportunities, and government support for MSMEs. The IFAS analysis results obtained a score of 2.48 and EFAS of 2.59, placing the MSME in Quadrant V of the IE Matrix with a hold and maintain strategy. Recommended strategies include increasing digital marketing, product and packaging innovation, strengthening business partnerships, increasing production capacity, and improving financial management and recording systems. The conclusion is that the integration of the Business Model Canvas and SWOT analysis can provide a comprehensive picture of the internal and external conditions of MSMEs and serve as a basis for formulating adaptive and sustainable business development strategies.  Keywords: Business Model Canvas, Business Development, Business Strategy